Experiential Tourism in Lake Toba Samosir District - ALFIFTO, Alfito; RINI, Endang Sulistya; ABSAH, Yeni (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).08, 2020)
Tourism is a new kind of industry that can accelerate economic growth and availability of employment, income increment, standards of living and stimulate other productive sectors. In the context of tourism, satisfaction is referred to, as part of the expectation before travel and experience after the trip. The satisfaction of tourists can be influenced by their experience in visiting tourism destinations. Experience can be the key to the success of tourism industry. The tourism experience is divided into two, namely experiential quality and experiential value. Tourists who visit Lake Toba will get their personal experience from their holiday. The satisfaction in enjoying Lake Toba will help those tourists consider if they would return or not. The purpose of this research is to analyze experiential quality impacts on tourist satisfaction through experiential value. The sampling method used is accidental sampling. The population of this research is domestic tourists who visit Lake Toba in Samosir District. The number of respondents in this study was 140. Data analysis is done through PLS-SEM by using SmartPLS 3.0 program. The results showed significant effects of experiential quality on experiential value, experiential quality on tourist satisfaction, experiential value on tourist satisfaction, and experiential quality on the satisfaction of tourists through experiential value.